Monofluoroalkene‐Isostere as a 19F NMR Label for the Peptide Backbone: Synthesis and Evaluation in Membrane‐Bound PGLa and (KIGAKI)3. Issue 7 (23rd January 2020) - Drouin, Myriam; Wadhwani, Parvesh; Grage, Stephan L.; Bürck, Jochen; Reichert, Johannes; Tremblay, Sébastien; Mayer, Marie Sabine; Diel, Christian; Staub, Alexander; Paquin, Jean‐François; Ulrich, Anne S.
Abstract: Solid‐state 19 F NMR is a powerful method to study the interactions of biologically active peptides with membranes. So far, in labelled peptides, the 19 F‐reporter group has always been installed on the side chain of an amino acid. Given the fact that monofluoroalkenes are non‐hydrolyzable peptide bond mimics, we have synthesized a monofluoroalkene‐based dipeptide isostere, Val‐Ψ[( Z )‐CF=CH]‐Gly, and inserted it in the sequence of two well‐studied antimicrobial peptides: PGLa and (KIGAKI)3 are representatives of an α‐helix and a β‐sheet. The conformations and biological activities of these labeled peptides were studied to assess the suitability of monofluoroalkenes for 19 F NMR structure analysis. Abstract : A 19 F NMR label was incorporated for the first time into a peptide backbone, by placing the isosteric monofluoroalkene into PGLa and (KIGAKI)3 . Its structural impact was thus characterized in an α‐helical and β‐stranded environment.